Response latex production at various times applications on rubber clone quick starter treated by stimulant ethylene banana peel - Andan Galingging; charloq charloq; Ferry Ezra Sitepu (Jurnal Agroekoteknologi, 2017)
Increasing latex production in rubber plants generally used ethrel stimulant that contains the chemical hormone ethylene and the ethrel may be difficult to consumed by the people's plantation (estates) because the price is expensive, and therefore it needed an alternative stimulant treatment. The purpose of this study was to evaluate the response latex production at various times applications on rubber clone quick starter treated by stimulant ethylene banana peel. The experiment was conducted for six months, began in September 2015 to Februari 2016 in Sungei Putih Rubber Research Institute, Galang Subdistrict, Deli Serdang regency. Three-Stage Nested Design was applied with three replications. The first step was time application, i.e., a first application, a second application, the second step of clone treatment, i.e., IRR 118 clone, PB 260 clone and the third step was stimulants, i.e., without stimulants, 50, 100, 150, and 200 g ethylene stimulant organic banana peel. Observed parameter was total solids content. The results showed that first application was more bigger than the second application to produced the latex. PB 260 clones were clones that experienced the highest increase in producing due to the provision treatment of stimulants. The stimulant extract 50 gram of the banana peel is stimulant that tends to increase production latex higher than others.  Increasing latex production in rubber plants generally used ethrel stimulant that contains the chemical hormone ethylene and the ethrel may be difficult to consumed by the people's plantation (estates) because the price is expensive, and therefore it needed an alternative stimulant treatment. The purpose of this study was to evaluate the response latex production at various times applications on rubber clone quick starter treated by stimulant ethylene banana peel. The experiment was conducted for six months, began in September 2015 to Februari 2016 in Sungei Putih Rubber Research Institute, Galang Subdistrict, Deli Serdang regency. Three-Stage Nested Design was applied with three replications. The first step was time application, i.e., a first application, a second application, the second step of clone treatment, i.e., IRR 118 clone, PB 260 clone and the third step was stimulants, i.e., without stimulants, 50, 100, 150, and 200 g ethylene stimulant organic banana peel. Observed parameter was total solids content. The results showed that first application was more bigger than the second application to produced the latex. PB 260 clones were clones that experienced the highest increase in producing due to the provision treatment of stimulants. The stimulant extract 50 gram of the banana peel is stimulant that tends to increase production latex higher than others.